New Voices: Gender-proofing cultural institutions: a case study on Project Arts Centre - Bok, Samantha (Irish Journal of Arts Management and Cultural Policy, 2019)
Examining the gendered conditions of cultural production, this case study of the Project Arts Centre proposes solutions to gender inequalities through the mobilisation of cultural institutions as Feminist spaces. Drawing from a long line of feminist scholarship, this paper examined gender relations at the Project Arts Centre, Dublin, identifying the gendered conditions under which cultural workers (both male and female) participate in contemporary cultural work. In the course of mapping gender relations at Project, an occupational gender division of labour was seen to still persist within the organization. It was also found that despite the existence of a hierarchy with a concentration of power at the top of the organisation, power relations at Project are largely perceived to be de-gendered and concealed by the ‘gender-neutral’ organisational ideology and culture of the workplace.The study proposes the deployment of feminist theory as an organisational resource for cultural organisations. It is suggested that a feminist approach to institutionalising gender equality, effectively mobilising the Project Arts Centre as a Feminist space through its artistic programme, is likely to provide the best solution to the gender inequalities identified